Computational analysis of solar thermal system with Prandtl nanofluid - Muhammad Imran Khan (614396) (2022)
The solar thermal system can address a large amount of heating and cooling load required by buildings and industry. To enhance the absorption efficiency in solar thermal systems, nanofluids are considered as promising heat transfer medium. The study presents a numerical study to investigate physical feature of the entropy production in hydro-magnetic reactive unsteady flow of Prandtl nanoliquid over an infinite plate. The heat expression is modeled subject to thermal radiation and magnetic field. Innovative characteristics slip mechanisms i.e., thermophoresis diffusion and Brownian motion are also accounted. Mathematical modeling of entropy production is described by employing thermodynamics law (second law). Furthermore chemical reactions takes place at surface of plate are implemented. Nonlinear system are converted to dimensionless form via suitable transformation. The resultant system is solved by numerical approach (finite difference method). Characteristics of thermal field, entropy rate, fluid flow and concentration are physical discussed through sundry parameters. The outcomes display that the maximum velocity field exists near the center of the surface, whereas the average time flow enhances the velocity distribution. An augmentation in thermal field is distinguished versus magnetic parameter, while reverse behavior holds for fluid flow. An increase in the thermal field with respect to the magnetic variable is noted, while the opposite effect is observed for the fluid flow. A larger approximation of radiation rises entropy rate and thermal field. Increasing the Brownian motion variable increases concentration, while reverse impact is observed for Schmidt number. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-022-13845-3